The structural integrity assessment of a liquid filled tank and the carrier vehicle during transportation, accident fall, and upon sudden brake application - Shah, Qasim Hussain (s.n, 2012)
Liquid cargo contained in a partially filled tank is known to experience sloshing movement when subjected to maneuvering disturbances. Large amplitude of liquid slosh can be induced within a partially filled road tank vehicle under mild to severe maneuvers, within may severely affect the structural integrity of the tank. A comprehensive experimental study is conducted within a scaled down model of a partially filled cylindrical tank without baffles to analyze the liquid slosh movement under longitudinal deceleration excitation. A three dimensional finite element analysis model of transient liquid slosh is developed for the partially filled cylindrical tank with and without baffles by using Arbitrary Lagrangian Eulerian (ALE)method available in LSDYNA program. The result of the experimental and simulation models of the transient liquid slosh, which demonstrates a good agreement. The liquid slosh characteristics are analyzed for half fill volume and subjected to sudden baking or deceleration excitation.